ANALISIS HUBUNGAN DURASI PAPARAN LAYAR (SCREEN TIME) TERHADAP KUALITAS TIDUR DAN TINGKAT KELELAHAN PADA MAHASISWA MENGGUNAKAN METODE PSQI DAN FSS: Program Studi Teknik Mesin, STTB Duta Bangsa - WIJAYANTI, FITRI RETNA (JUS TEKNO (Jurnal Sains dan Teknologi), 2025)
This study aims to analyze the relationship between screen time duration, sleep quality, and fatigue levels among university students. The research employed a quantitative method with a descriptive approach. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI), while daily activity alertness was assessed using the Epworth Sleepiness Scale (ESS). Data were collected over a 15-day period through periodic questionnaire responses from four university students. The results indicated a decrease in both PSQI and ESS scores from the first to the third week. The reduction in PSQI scores reflects improved sleep quality, while the decrease in ESS scores indicates reduced daytime sleepiness and increased daily activity alertness. These findings suggest a relationship between sleep quality and daily activity levels. In conclusion, better management of screen time duration has the potential to improve sleep quality and reduce fatigue levels among university students. Keywords: screen time, sleep quality, PSQI, ESS, fatigue, university students